Perbedaan Laju Aliran Saliva dan pH Karena Pengaruh Stimulus Kimiawi dan Mekanis - Tecky Indriana (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2011)
AbstractThe aim of this research is to identify the effect of chemical and mechanical stimulus on salivary flow rate and pH saliva. This study involved 10 young-adult subjects of Faculty of Dentisry, Jember University. Then , through sepitting method, secretion saliva speed was measured and pH saliva without stimulus and was campared with chemical and mechanical stimulated secretion.. Results showed that there is a significant difference in salivary flow rate and pH saliva without stimulus and that of stimulated secretion (chemical and mechanical).Key Words: Salivary Flow rate , Ph Saliva, mechanical stimulus, chemical stimulus.